Determinants of Commercial Banks' lending Behavior: Evidence from Turkey - TOMAK, Serpil (Asian Journal of Empirical Research, 2013)
This paper studies the bank-level (size and access to funds) and market-based (interest rate, inflation rate, GDP) variables’ impact on bank lending behavior in Turkey using quarterly bank level data of 15 private commercial banks and 3 state-owned banks for the 2003-2012 period. The empirical results indicate that banks’ business loans performance depends on its size, total liabilities,nonperforming loans to total loans (NPL) and inflation rate. Besides, ownership structure also affects the total business loans behavior. The results suggest that private banks loans performance is better than the state-owned commercial banks.